PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMENPADA PT. BUS RAJA PERDANA INTI (RAPI) PEKANBARU (STUDI PADA DEPARTEMEN PEMASARAN) - Dedi Arnanda; Meyzi Heriyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted at PT. Raya Perdana Inti Pekanbaru, located on HR Street. Soebrantas Km, 18. Pekanbaru, Riau. The purpose of this study was to determine the effect of service quality and price on customer satisfaction of transportation services at PT. Raja Perdana Inti Pekanbaru partially and simultaneously. In this research the method used is quantitative descriptive analysis with SPSS program. The population in this study are all passengers who use transportation services at PT. Rja Perdana Inti Pekanbaru in the last year of 2018 totaling 30,976 people. Where the samples in this study are consumers of PT. Raja Perrdana Inti Pekanbaru as many as 100 respondents. To determine the sample using the Slovin formula. Data collection techniques through questionnaires and interviews, types and sources of data using primary data and secondary data, measurement collection techniques using a Likert scale.From the analysis of data which includes validity, reliability, simple linear regression analysis, multiple linear analysis, determination analysis and significance test with t test (partial test), and f test (simultaneous). The results of this study indicate that the results of the first t test hypothesis testing, service quality on customer satisfaction is t arithmetic (12,879)> t table (1,6605) means that service quality has a significant effect on customer satisfaction. Second, the price of customer satisfaction is t arithmetic (12,879)> t table (1.6605) means that the price significantly influences customer satisfaction. The f test results of service quality and price have a significant effect on customer satisfaction, namely f arithmetic (93,974)> F_ table (3.09). This means that service quality and price simultaneously have a significant effect on customer satisfaction at PT. Raja Perdana Inti Pekanbaru.Keywords:Service Quality, Price, Consumer Satisfaction